The Cartelization of World Commodity Markets - Pindyck, Robert S. (American Economic Review, 1979)
The cartelization of world commodity markets is not a new phenomenon. In a historical survey of the experience of some international commodity cartels, Paul L. Eckbo shows that at one time or another there has been an attempt to cartelize the market for most of the major internationally traded commodities. The large majority of these attempts at cartelization, however, were failures-the cartel either dissolved after a short period of time, or in some cases the cartel remained in force officially, but had little or no real impact on price and member revenues. Of the fifty-one formal cartel organizations documented by Eckbo, only nineteen could be considered successful in the sense of being able to maintain a price significantly higher than what it would have been in the absence of agreements. But even the successful cartels were limited in their durability; the average lifetime of the formal agreements was about five years, and only five of the nineteen cartels lasted ten years or longer. What is new is the growing concern that the prospects for successful cartelization have suddenly become greater, and that in the future, world commodity markets are likely to be increasingly dominated by cartels. Much of this concern, of course, has been the result of the Organization of Petroleum Exporting Countries' (OPEC) spectacular success in quadrupling world oil prices, and the International Bauxite Association's (IBA) success in tripling the price of bauxite. Warranted or not, this concern now casts a shadow over predictions, policy prescriptions, and proposals for the international management of commodity markets. Buffer stocks and other instruments for price stabilization, for example, become the vehicles for cartelization and the establishment and maintenance of the monopoly price. And for some, cartelization, or more specifically, an implicit or explicit transfer of monopoly and monopsony power from developed to developing countries, is an essential and justifiable component of the New International Economic Order (NIEO). ' Given the historical success record of international cartels, is there any reason to expect new attempts at cartelization to succeed where similar attempts in the past have failed? Has the structure of world commodity markets-or the environment surrounding them-changed in such a way as to better facilitate the formation and success of cartels, so that over the next decade we are likely to witness a proliferation of international cartels that will succeed in raising the prices of a large number of key commodities? There are no simple answers to these questions. While the interest in cartelization on the part of some LDCs may indeed be greater, there appears to be no clear change in the structure of commodity markets that would facilitate their cartelization. It is difficult to agree with C. Fred Bergsten's assertion, for example, that the environment has shifted to one in which supplies of raw material commodities are shrinking as demand keeps growing, thereby encouraging cartelization. In the past some cartels succeeded while others failed for reasons specific to each market and to each cartel configuration. As a more recent example, IBA succeeded while CIPEC, the copper cartel, did not-and